Evaluation of a mammography decision aid for women 75 and older at risk for lower health literacy in a pretest-posttest trial. Issue 9 (September 2021) - Cadet, Tamara; Aliberti, Gianna; Karamourtopoulos, Maria; Jacobson, Alicia; Gilliam, Elizabeth A.; Primeau, Sara; Davis, Roger; Schonberg, Mara A.
Highlights: Decision aids need to be evaluated with older women at risk for low health literacy. Mammography decision aids are helpful for older women at risk for low health literacy. Women of all literacy levels need tools to participate in screening decisions. Abstract: Objective: The evaluation of the effect of a mammography decision aid (DA) designed for older women at risk for lower health literacy (LHL) on their knowledge of mammography's benefits and harms and decisional conflict. Methods: Using a pretest-posttest design, women > 75 years at risk for LHL reviewing a mammography DA before and after their [B] primary care provider visit. Women were recruited from an academic medical center and community health centers and clinics. Results: Of 147 eligible women approached, 43 participated. Receipt of the DA significantly affected knowledge of mammography's benefits and harms [B] (pre-test ( M = 3.75, SD = 1.05) to post-test ( M = 4.42, SD = 1.19), p = .03). Receipt of the DA did not significantly affect decisional conflict (pre-test ( M = 3.10, SD = .97) to post-test ( M = 3.23, SD = 1.02), p = .71, higher scores = lower decisional conflict). The majority of the women (97%) indicated that the DA was helpful. Conclusions: Women found a mammography screening DA helpful and its use was associated with these women having increased knowledge of mammography's benefits and harms. Practice Implications: With the shift toward shared decision-making for women > 75 years, there is a need to engage women of all literacy levels to participate in these decisions and have tools such as the one tested in this study.